Ekologi dan Agama: Menelusuri Perubahan Ekologi di Asia Tenggara Maritim - Shofiyanti, Lilis (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2025)
This article reviews Faizah Zakaria’s book, The Camphor Tree and the Elephant: Religion and Ecological Change in Maritime Southeast Asia (2023). The book investigates the interactive role of religion and colonialism in shaping ecological change in the North Sumatran Highlands and the Malay Peninsula during the “long nineteenth century.” Zakaria introduces the “spiritual Anthropocene,” arguing that human domination over the planet is inextricably linked to the spiritual transformation. She contends that religious conversion to modern forms of monotheism (Islam and Christianity), accelerated by colonial rule, created a sociopolitical ecology that radically eliminated the “spiritual appeal” (enchantment) of nature. This disenchantment process propelled a transition to a cash economy that prioritized transactions over ritualistic kinship, and relocated ecological authority to elites. Through material case studies of the camphor tree (Dryobalanops aromatica) and the elephant, the book demonstrates how the rationalization of nature by modern monotheistic religions contributed to the accelerated environmental degradation and the loss charisma of non-human beings.